END-USERS NEED INFORMATION TOO! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Most people involved in development would agree that to develop new technologies is not enough in itself: ways have to be found of getting new ideas, management practices and materials out to potential users. Not just to a small number of...